Intradermal Hepatitis B Vaccination in Non-responder People Living with Human Immunodeficiency Virus in Japan - Yoshimura, Yukihiro; Sasaki, Hiroaki; Miyata, Nobuyuki; Tachikawa, Natsuo (Japanese Journal of Infectious Diseases, 2022)
We performed a pilot study to assess the immunogenicity and safety of intradermal hepatitis B (HB) virus vaccines in people living with HIV (PLWH). This single-center prospective study was conducted in Yokohama, Japan. Adult PLWH with serum antibodies against HB surface antigen (anti-HBs) <10 mIU/mL at all time points after standard HB vaccination were included. We administered HB surface antigen (total dose of 10 μg) at 5 separate sites intradermally at baseline, one month, and 6–9 months and measured anti-HBs 1–3 months after administration. Eleven PLWH were included in this study. The mean age was 36 years, and all patients were men. At baseline, all patients were on antiretroviral therapy, and the mean CD4+ lymphocyte count was 588 /μL and plasma HIV-RNA was <20 copies/mL, except for one patient. Anti-HB levels were elevated to >10 mIU/mL in one patient after one dose, 6 patients after 2 doses, and 4 patients after 3 doses of the intradermal vaccines. Eight patients experienced grade 1 local adverse events. Additional vaccination via the intradermal route induced an anti-HBs level >10 mIU/mL in all patients, without serious adverse events.